PENGARUH SUBSTITUSI TEPUNG TALAS TERHADAP KUALITAS KULIT PIE - Mustika, Dina; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
The background of this study is to reduce the dependence of imported materials (wheat), improve the utilization of local foodstuffs and improve the utilization of taro. This study aims to analyze the influence of substitution of taro flour by 25%, 50% and 75% to the quality of pie skin which includes shape, color, texture, aroma and taste. Types of pure experimental research with complete randomized design methods. The dependent variable of skin quality of pie by using primary data sourced from 5 expert panelists by proposing the organoleptic test format. Analyze data with ANAVA, if Fcount> Ftable then proceed with Duncan test. The result of this research is that there is no significant effect of substitution of flour taro on the quality of pie skin (form, crispy texture and taste) because Fhitung <Ftabel, and there is significant influence from substitution of taro flour to pie skin quality (color, aroma, and taro flavor) because Fcount> Ftable. The best result based on organoleptic test is found in X3 with taro flour substitution of 75%.Keywords: Influence, Substitution, Taro Flour and Leather Pie.